PRACTICE-ORIENTED EDUCATION IN SCHOOL MATHEMATICS (Journal of Educational Sciences, 2020)
The article is devoted to the problems of teaching mathematics in a school with practiceoriented content. The aim of the study is to develop a methodology for teaching students to solve problems with practical content in the process of implementation of practice-oriented teaching mathematics. The development of students ‘ abilities to solve practice-oriented problems in the process of teaching mathematics should be considered as one of the ways of forming their mathematical competence. Practice-oriented tasks are understood as mathematical tasks, the content of which describes the situation of reality associated with the formation of practical skills of using mathematical knowledge and skills needed in everyday life. The solution of this type of problem is largely based on the construction of a model of the real situation described in a particular problem. This model of compilation requires a high level of mathematical training and is the result of training that is appropriately called culture-universal. The constant use of practice-oriented tasks in teaching mathematics at school will allow the learner to generalize and deepen knowledge, acquire skills and knowledge on the subject, be able to link the learning process with the real conditions of life, to show initiative and independence. The researchers describe didactic goal-setting and examples of practice-oriented tasks in mathematics developed by the authors. Monitoring of learners ‘ activities indicates that the frequent use of practice-oriented tasks increases the interest of learners in educational activities, forms a positive motivation in the classroom Key words: secondary school mathematics, practice-oriented tasks, motivation.